The Economics of Lockdown. (30th November 2020) - Besley, Timothy; Stern, Nicholas
Abstract: In this paper, we suggest an approach to analysing policies relating to the COVID‐19 pandemic. We discuss the formulation of policy and sketch how the approach can be applied to different specific challenges as policymakers try to make difficult choices for managing the pandemic and protecting the economy and society.